Real-world anaplastic lymphoma kinase (ALK) rearrangement testing patterns, treatment sequences, and survival of ALK inhibitor-treated patients. (4th March 2019) - Davies, Jessica; Martinec, Michael; Coudert, Mathieu; Delmar, Paul; Crane, Gracy
Abstract: Background: The anaplastic lymphoma kinase (ALK) treatment landscape is crowded following recent ALK inhibitor approvals, and updated information on real-world treatment patterns in advanced non-small-cell lung cancer (aNSCLC) with ALK rearrangement ( ALK+ ) is needed. Methods: This retrospective US cohort study used Flatiron Health's longitudinal electronic health record (EHR)-derived database. Patients (≥ 18 years old) diagnosed with stage IIIB/IV aNSCLC, with documented ALK rearrangement and ≥2 visits after January 1, 2011 were followed until February 28, 2016. Patients enrolled on a clinical trial or exposed to ALK inhibitors other than crizotinib or ceritinib were excluded. Treatment patterns, time and type of biomarker testing, and overall survival (OS) were analyzed. Results: Median age ( n = 300) was 62.5 years; 55% female; 48% non-smokers; 8.7% central nervous system (CNS) metastases at diagnosis. Overall, 73% and 86% received their first ALK biomarker test before/at diagnosis, or before/during first-line treatment, respectively. In total, 90.0%, 78.1%, and 74.7% received first-, second-, and third-line therapy, respectively. Most patients received ALK-targeted treatment; 62% received crizotinib, of which 21% reported a dose reduction. Progression was the most common reason for crizotinib (78%) and ceritinib (41%) discontinuation. Median OS was 29.4 months (95% CI =24.7–39.6) overall; 27.1 months (95% CI =22.0–35.0) in patients with CNS metastases, and 36.9 months (95% CI =25.1–not reached) without. Conclusions: Despite widespread crizotinib use in patients with ALK + aNSCLC, a high proportion of patients progressed. Ongoing analyses of EHR-derived cohorts are valuable in assessing real-world testing rates and therapeutic use of ALK inhibitors.